Financing the Future : Infrastructure Needs in Latin America, 2000-05 - Fay, Marianne (World Bank, Washington, DC, 2014)
To assess five-year demand for infrastructure investment in Latin America and the Caribbean, and the private sector's role in meeting this demand, the author developed a model to predict future demand for infrastructure - defined as what consumers and producers would ask for, given their income and level of economic activity. Overall projections over the next five years: a) A doubling of telephone mainlines per capita. b) A steady increase in electricity generating capacity. c) Small increases in water and sanitation coverage. d) Steady expansion of road infrastructure, with rail transport becoming less important. Investments of $57 billion annually for 2000-05 (roughly 2.6 percent of Latin America's GDP) are expected to be absorbed largely by electricity ($22 billion), roads ($18 billion), and telecommunications ($ 6 billion). A surge in private finance of infrastructure in recent years (roughly $35 billion in 1998, excluding divestiture payments) has disproportionately favored telecommunications ($14 billion) and transport ($12 billion). Private investment exceeds predicted need for telecommunications (although the model did not include costs associated with the emergence of cellular phones), covers about half the demand for roads, and meets just a fraction of needs in power and water and sanitation - where there will be a shortfall in investments. Projections are likely to be on the low side because they cover new investments, not rehabilitation or maintenance.